2019
DOI: 10.1007/s40279-019-01179-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Physical Exercise Training in the Workplace on Physical Fitness: A Systematic Review and Meta-analysis

Abstract: Background 2 There is evidence that physical exercise training (PET) conducted at the workplace is effective in improving 3 physical fitness and thus health. However, there is no current systematic review available that provides high-4 level evidence regarding the effects of PET on physical fitness in the workforce.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 67 publications
3
23
0
1
Order By: Relevance
“…However, both groups, CT and BW, showed some improvements (of 8.1% and 7.5%, respectively) in the cardiorespiratory fitness test, with a group × time effect ( Table 3). This is consistent with a recent meta-analysis that found improvements in this parameter with programs lasting 9-12 weeks [17]. Nonetheless, the same meta-analysis did not find any improvement when the programs were of 3 sessions/week, with each session lasting 16-30 min.…”
Section: Measurementssupporting
confidence: 90%
See 1 more Smart Citation
“…However, both groups, CT and BW, showed some improvements (of 8.1% and 7.5%, respectively) in the cardiorespiratory fitness test, with a group × time effect ( Table 3). This is consistent with a recent meta-analysis that found improvements in this parameter with programs lasting 9-12 weeks [17]. Nonetheless, the same meta-analysis did not find any improvement when the programs were of 3 sessions/week, with each session lasting 16-30 min.…”
Section: Measurementssupporting
confidence: 90%
“…However, other studies found no clear evidence of any improvement in employees' mental health when the interventions applied were based on physical exercise programs [15]. In this sense, physical exercise programs have shown improvements in pain located in specific areas of the body, such as the lower back [16], and they have managed to improve cardiorespiratory fitness and muscular endurance [17]. Similarly, they have been shown to be effective in reducing the levels of depression [18], and anxiety [19].…”
Section: Ijomeh 2021;34(1)mentioning
confidence: 99%
“…They usually have a short duration, with both preventive and therapeutic approaches, avoiding overloading or leading the employee to fatigue. It is a physical activity based on exercises to compensate repetitive movements, the absence of movement, or uncomfortable postures assumed during the working period [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization (WHO, 2021) considers workplace wellness programs (WWP) important to both physiological and psychological health of employees while having both financial and productivity benefits to employers. Although WWP's have shown preliminary efficacy (Burn et al, 2019;Emerson et al, 2017;Prieske et al, 2019;Rezai et al, 2020), the COVID-19 pandemic and associated social distancing orders required that some non-essential employees work from home (Guan et al, 2020). These orders presented a significant challenge to WWP's that have participants attend their sessions in fitness centers with their peers.…”
Section: Introductionmentioning
confidence: 99%